Preferential trading arrangements in agricultural and food markets the case of the European Union and the United States - Gallezot, Jacques; Bureau, Jean-Christophe (Organisation for Economic Co-operation and Development, 2005)
Developing countries are concerned that multilateral tariff reductions will harm their agricultural sectors because of preference erosion. The findings in this report suggest that although this may indeed be a problem for some countries in some sectors, factors other than preferential schemes may be limiting developing country exports. The report provides information on the extent to which developing countries have used selected, non-reciprocal preferential trading schemes provided by the EU and the US. Secondary data are complemented by interviews with market operators further clarifying the empirical findings. A special section has been devoted to the preferences granted to African countries highlighting the conditions for this set of developing countries.--Publisher's description.